A Preliminary Study of the Effect of Hyperadrenocorticism on Calcium and Phosphate Concentrations, Parathyroid Hormone and Markers of Bone Turnover in Dogs - Mooney, Carmel T.; Shiel, Robert E.; Sekiya, Mary; Dunning, Mark; Gunn, Eilidh (Frontiers in Veterinary Science, 2020)
Reports on the effects of hyperadrenocorticism (HAC) on bone turnover in dogs are largely confined to radiographic studies. The aim of this study was to more accurately assess bone turnover in dogs with HAC by measuring circulating total and ionized calcium and phosphate concentrations, both intact and whole parathyroid hormone (PTH) concentrations and markers of both osteoblastic (osteocalcin) and osteoclastic [carboxyterminal cross-linked telopeptide of type 1 collagen (ICTP) and urine aminoterminal telopeptide of type 1 collagen (NTX) activity]. Dogs with HAC and a control group were prospectively enrolled for comparison. Results from 49 dogs with HAC were compared with 39 dogs from a hospital control population. Plasma intact and whole PTH concentrations were determined using a human immunoradiometric assay. Serum osteocalcin and NTX concentrations were measured using human enzyme linked immunosorbent assays. Serum ICTP concentration was measured using a human radioimmunoassay. Total calcium concentrations in dogs with HAC (2.67 ± 0.25 mmol/L) were not significantly different than in the control group (2.67 ± 0.14 mmol/L). By contrast, phosphate concentrations were significantly (P = 0.0143) higher in dogs with HAC (1.46 ± 0.30 mmol/L) compared to the control group (1.28 ± 0.33 mmol/L). The median intact PTH concentration in HAC dogs was 9.25 (range, 1.34–95.45) pmol/L, which was significantly (P < 0.0001) higher than in the control group [median, 3.88 (range, 2.01–10.31) pmol/L]. Whole PTH concentrations were also significantly (P < 0.0001) higher in the HAC group [median, 4.61 (range, 0.56–125.16) pmol/L] compared to the control group [median, 1.83 (range, 0.88–6.81) pmol/L]. Serum osteocalcin and urine NTX concentrations were not significantly different between the two groups of dogs. The median ICTP concentration in dogs with HAC was 2.98 (range, 1.15–6.62) ng/mL which was significantly (P < 0.0001) lower than in the control dogs [median, 7.30 (range, 3.68–21.25) ng/mL]. Both whole and intact PTH concentrations are increased in dogs with HAC compared to a hospital control population. This does not however appear to be associated with a decrease in bone formation (as assessed by osteocalcin) or an increase in bone resorption (as assessed by ICTP and urine NTX).